Determining the Energy Efficiency in Cotton Production: A Case of Adana Province - Ali BOLAT (ISPEC Journal of Agricultural Sciences)
This study has been conducted to calculate the energy efficiency of cotton production held under the conditions of Adana/Turkey in 2020 and 2021. Basic data such as the economic life, work success, fuel and oil consumption and weights of the tools-machines used in the study as well as the fertilizer and seed amounts were obtained from the current measurements, other studies, various sources and catalogues. The study has concluded that the highest rate among the energy equivalents of the inputs used in cotton production belonged to the fertilizer energy input with 44.43%. This rate was followed by fuel-oil energy input with 23.68%. In cotton production, the energy output/input ratio years has been calculated as 2.33 and 2.26, the specific energy value as 5.06 MJ kg-1 and 5.21 MJ kg-1, the energy productivity value as 0.20 kg MJ-1 and 0.19 kg MJ-1, and the net energy efficiency as 36082.21 MJ ha-1and 34194.21 MJ ha-1.